Diagnostic and economic evaluation of a point-of-care test for respiratory syncytial virus. Issue 3 (17th August 2020) - Allen, A. Joy; Gonzalez-Ciscar, Andrea; Lendrem, Clare; Suklan, Jana; Allen, Karen; Bell, Ashley; Baxter, Frances; Crulley, Stephen; Fairlie, Louise; Hardy, Danielle; Johnston, Louise; McKenna, Joanne; et al.
Respiratory syncytial virus is a common cause of bronchiolitis. Historically, point-of-care tests have involved antigen detection technology with limited sensitivity. The aim of this study was to prospectively evaluate the diagnostic accuracy and model the economic impact of the Roche cobas® Liat® point-of-care influenza A/B and respiratory syncytial virus test. The "DEC-RSV" study was a multi-centre, prospective, observational study in children under 2 years presenting with viral respiratory symptoms. A nasopharyngeal aspirate sample was tested using the point-of-care test and standard laboratory-based procedures. The primary outcome was accuracy of respiratory syncytial virus detection. The cost implications of adopting a point-of-care test were modelled using study data. A total of 186 participants were recruited, with both tests performed on 177 samples. The point-of-care test was invalid for 16 samples (diagnostic yield 91%) leaving 161 available for primary analysis. After resolving discrepancies, the cobas® Liat® respiratory syncytial virus test had 100.00% (95% CI 96.07%–100.00%) sensitivity and 98.53% (95% CI 92.08%–99.96%) specificity. Median time to result was 0.6 h (interquartile range (IQR) 0.5–1) for point-of-care testing and 28.9 h (IQR 26.3–48.1) for standard laboratory testing. Estimated non-diagnostic cost savings for 1000 patients, based on isolation decision-making on point-of-care test result, were £57 010, which would increase to £94 847 when cohort nursing is used. In young children the cobas® Liat® point-of-care respiratory syncytial virus test has high diagnostic accuracy using nasopharyngeal aspirates (currently an off-licence sample type). Time to result is clinically important and was favourable compared to laboratory-based testing. The potential exists for cost savings when adopting the point-of-care test. This prospective evaluation of the cobas Liat point-of-care RSV test in children demonstrated high diagnostic accuracy using nasopharyngeal aspirate samples, with favourable time to result compared to usual laboratory-based testing procedures https://bit.ly/2yKKmUB